The Universities (Discipline Of Students) Rules: An Administrative Law Perspective - Gan, Ching Chuan (Journal of Malaysian and Comparative Law, 2019)
This article will attempt to examine and discus the students' disciplinary rules of the local universities from the perspective of administrative law. Attention will be focused on the University of Malaya (Discipline of Students) Rules, 1975. The other local universities established under the Universities and University Colleges Act, 1971, too have similar rules. The subject matter included herein are the composition and jurisdiction of the disciplinary authority, the delegation of power by the disciplinary authority, the disciplinary offences, the procedure of prosecuting disciplinary offence, the types of punishment that can be imposed by the disciplinary authority, and appeals against the decisions of the disciplinary authority.